Pengaruh Online Costumer Review dan Affiliate Marketing Terhadap Keputusan Pembelian pada Tiktok Shop di Kota Bima (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of online customer reviews and affiliate marketing on purchasing decisions at TikTok Shop in Bima City. The study used a quantitative approach with a survey method of 112 respondents who had made purchases through TikTok Shop. The sampling technique used purposive sampling. Data were collected using a Likert scale questionnaire that measured respondents' perceptions regarding online customer reviews, affiliate marketing, and purchasing decisions. Data analysis was performed using multiple linear regression with the help of SPSS version 25. The results showed that online customer reviews and affiliate marketing had a positive and significant effect on purchasing decisions, both partially and simultaneously. These findings indicate that informative and credible customer reviews and effective affiliate marketing strategies can increase consumer confidence in making purchasing decisions at TikTok Shop. In addition, both variables make a significant contribution in explaining variations in consumer purchasing decisions. The results of the study emphasize the importance of managing customer reviews and optimizing affiliate marketing programs as digital marketing strategies to improve purchasing decisions on e-commerce platforms.